BMP2 Is Related to Hirschsprung’s Disease and Required for Enteric Nervous System Development - Huang, Sizhou; Wang, Yi; Luo, Lingfei; Li, Xiaoqing; Jin, Xianqing; Li, Shuangshuang; Yu, Xiaoping; Yang, Min; Guo, Zhenhua (Frontiers in Cellular Neuroscience, 2019)
The enteric nervous system (ENS) is derived from neural crest cells (NCCs). Defects in ENS NCCs colonizing the intestines lead to an absence of enteric ganglia in the colon and results in Hirschsprung's disease (HSCR). Bone morphogenetic proteins (BMPs) play diverse roles in the proliferation, migration and survival of ENS NCCs; however, whether BMPs are involved in HSCR and the underlying mechanism remains largely unknown. In this study, we found that BMP2 expression is significantly decreased in HSCR patients. Further experiments demonstrated that BMP2 is involved in the regulation of NCC proliferation, migration and differentiation. In a detailed analysis of the role of BMP2 in HSCR development in vivo, we demonstrated that BMP2b regulates the proliferation, migration and differentiation of vagal NCCs in zebrafish and that BMP2b is required for intestinal smooth muscle development. In addition, we showed that BMP2b is involved in regulating the expression of glial cell line-derived neurotrophic factor (GDNF) in the intestine, which mediates the regulation of ENS development by BMP2b in zebrafish. These results highlight a central role of the BMP-GDNF cascade in intestinal patterning and ENS development. Our results further demonstrate the key role of BMP2 in the aetiology of HSCR in vitro and in vivo.